From Interior to Interiority: Locating Key Historical Moments in the Relationship between Spaces and Individuals - Petit, Bruno Cruz (UI Scholars Hub, 2019)
We spend increasingly more time in architectural interiors, spaces that can give us quality of life and interesting scenarios for the growth of identity and interiority. However, both spatial interior and psychological interiority faces difficulties inherent to contemporary life. This text proposes a critical review of the literature on the socio-spatial archeology of the subject in order to see possible paths of realisation of interiority in the present. The document presents several stages in the sociocultural evolution of an interior space that needs to be described with different adjectives (spiritual, hedonistic, promiscuous) and groups the most relevant contributions of the literature according to this proposal.